2022
DOI: 10.1097/pas.0000000000001958
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Prognostic Features of Pediatric Follicular Cell–derived Thyroid Carcinomas

Abstract: Pediatric thyroid carcinomas (TCs) are rare and mainly approached based on data extrapolated from adults. We retrospectively reviewed 222 pediatric TCs (patient age less than or equal to 21 y). Lymph node (LN) disease volume at presentation was considered high if the largest positive LN measured ≥1 cm and/or >5 LNs were positive. High-grade follicular cell–derived thyroid carcinoma (HGFCTC) were defined by the presence of marked mitotic count and/or tumor necrosis and considered as high-risk histology along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
1
1
2
Order By: Relevance
“…Our study also revealed a positive correlation between the presence of ETE and CLNR, yet ETE did not show a significant relationship with recurrence in univariate analysis. This is consistent with some studies ( 16 , 26 ) but contrasts with others, including Jeon et al.’s work, which identified ETE as an independent predictive factor for recurrence ( 10 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our study also revealed a positive correlation between the presence of ETE and CLNR, yet ETE did not show a significant relationship with recurrence in univariate analysis. This is consistent with some studies ( 16 , 26 ) but contrasts with others, including Jeon et al.’s work, which identified ETE as an independent predictive factor for recurrence ( 10 ).…”
Section: Discussionsupporting
confidence: 91%
“…In a recent meta-analysis, 12 the estimated frequency of HGDTC-TC was 19% in tumours showing tall cell features based on 89 cases from five studies. [6][7][8][9]13 This estimated proportion was significantly higher than the observed 5.3% rate in the current study, possibly due to the small number of cases included in the meta-analysis. Prior to the WHO 5th edition, 4 mitotic count and tumour necrosis were not routinely evaluated and reported in daily practice or in studies of thyroid carcinoma, including PTC-TC.…”
Section: Discussioncontrasting
confidence: 81%
“…In this study, we have shown that HGDTC‐TC is relatively rare, accounting for only 5% of all differentiated thyroid carcinomas containing at least 30% tall cell area. In a recent meta‐analysis, 12 the estimated frequency of HGDTC‐TC was 19% in tumours showing tall cell features based on 89 cases from five studies 6–9,13 . This estimated proportion was significantly higher than the observed 5.3% rate in the current study, possibly due to the small number of cases included in the meta‐analysis.…”
Section: Discussioncontrasting
confidence: 58%
“…As in adults, papillary thyroid carcinoma is the most common histologic type of pediatric follicular cell-derived thyroid carcinoma [1,2]. Despite morphologic similarities, pediatric papillary thyroid carcinomas (PPTCs) differ from their adult counterparts [2][3][4] with respect to genomic alterations (e.g., high prevalence of oncogene fusions, overall lower frequency of BRAF p.V600E and RAS-mutations, universally reported absence with only exceptional occurrence of TERT promoter mutations, increased frequency of inherited neoplasia associated somatic and/or germline pathogenic variants) and distinct clinical and pathological features (e.g., higher frequency for lymph node and/or distant metastases, ionizing radiation-induced pathogenesis, better overall prognosis compared to adults with similar features, lower fraction of tall cell PTC, and higher frequency of diffuse sclerosing PTC) [1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These observations have made PPTC an area of continued interest in thyroid neoplasia.…”
Section: Introductionmentioning
confidence: 99%